Intergenerational Social Mobility and Assortative Mating in Britain - John Ermisch; Marco Francesconi (Institute for the Study of Labor (IZA), 2002)
This paper investigates the links between the socio-economic position of parents and the socio-economic position of their offspring and, through the marriage market, the socioeconomic position of their offspring?s parents-in-law. Using the Goldthorpe-Hope score of occupational prestige as a measure of status and samples drawn from the British Household Panel Survey 1991-1999, we find that the intergenerational elasticity is around 0.2 for men and between 0.17 and 0.23 for women. On average, the intragenerational correlation is lower, and of the order of 0.15 to 0.18, suggesting that the returns to human capital, which is transmitted across generations by altruistic parents, contribute more to social status than assortative mating in the marriage market. Substantially higher estimates are reported when measurement error is accounted for. We also find strong nonlinearities, whereby both inter- and intra-generational elasticities tend to increase with parental status. We offer four possible explanations for this finding, three of which – one based on mean-displacement shifts in the occupational prestige distribution, another based on life-cycle effects and the third based on differential measurement errors – do not find strong support in our data. The fourth explanation is based on the notion of intergenerational transmission of social capital and intellectual capital. The evidence supports the idea that richer parents are likely to have a larger and more valuable stock of both social capital and intellectual capital to pass on to their children.
Keywords: I20; D64; D31; J12; 330; Intergenerational links; marriage market; assortative mating; Goldthorpe-Hope occupational prestige index; social and intellectual capital; Soziale Mobilität; Generationenbeziehungen; Familienökonomik; Humankapital; Erwerbsstatus; Schätzung; Großbritannien